Ritual Larung Sembonyo Sebagai Mekanisme Sosio-Ekologi Masyarakat Nelayan Pantai Popoh Tulungagung - Anindya Roikhatul Jannah; Ayu Rahma Wati; A. Zahid (CV. SINAR HOWUHOWU, 2026)
This article examines the Larung Sembonyo ritual at Popoh Beach, Tulungagung Regency, East Java, as a socio-ecological system based on local wisdom that goes beyond its ceremonial function. Using a qualitative phenomenological approach and a Traditional Ecological Knowledge (TEK) framework, this study examines the mechanisms of reproductive rituals in maintaining the sacredness of the sea alms tradition and enabling the formation of social relationships and ecological awareness among local fishermen. Data were obtained through in-depth interviews with the head of the Popoh Beach fishermen's yard and field observations. The results show that Larung Sembonyo operates through three main dimensions: spiritual, ecological, and social. The spiritual dimension is reflected in cosmological respect for the sea, the ecological dimension is evident in the three-day fishing ban and the use of natural offerings as a conservation mechanism, while the social dimension is seen in the fencing of communal solidarity. The sustainability of the ritual is supported by moral and spiritual sanctions based on customary prohibitions, a system of independent contributions from fishermen, and the involvement of the younger generation as a cultural regeneration strategy. The main challenges come from pressure from religious purification groups and the weakening of the spirit of mutual cooperation due to modernization. These findings confirm that Larung Sembonyo is an adaptive socio-ecological mechanism that integrates local ecological knowledge, cosmological ethics, and social capital.